Chemical and biological characterization of antibacterial compounds present in Ochna pretoriensis (Ochnaceae) leaf extracts - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.